Are Women a Missing Audience for Science on YouTube? An Exploratory Study - Landrum, Asheley R. (Frontiers in Communication, 2021)
Educational science programming on digital video platforms such as YouTube wrestle with sometimes significant gender disparities in viewership. When men engage with science and technology content on digital platforms more than women, gender gaps in the understanding of, engagement with, and interest in STEM may intensify. Therefore, there is a critical need for research aiming to aid in our understanding of these gender differences. This study provides evidence that the gender gaps may exist not in the use of YouTube itself, but in the engagement with science and technology content on the platform. Furthermore, there are gender differences in the reasons for engaging with such content, with women, perhaps, more motivated by instrumental purposes than to satisfy their science curiosity.